Women’s Empowerment for Sustainable Agriculture Development - S.K. Santra; Rubi Kundu (Journal of Agricultural Extension Management, 2025)
In a stratified society like ours access and empowerment of different section of the societies are becoming serious concerns and to address it planners, managers, social scientist all over the world have started deliberating and devising way out like anything. In this direction genders issues are dominating over other vulnerable issues like poverty, class conflicts, communities, ethnic issues etc. In ensuring an egalitarian development gender equity still remains as a pertinent question as it has been for the thousands of years of human civilization